ANTIBACTERIAL ACTIVITY OF PROPOLIS Trigona spp. FROM BUKITTINGGI WEST SUMATERA AGAINST Salmonella sp. - Hasan, Zaenal (Sam Ratulangi University, 2011)
Propolis is a resinous hive product consists of exudates from plants mixed with beeswax and used by bees asglue. The objective of this study was to investigate the antibacterial activity of ethanol extract of Trigona spp.propolis collected from Bukittinggi West Sumatera on Salmonella sp. using agar well diffusion method. Thecompound group of the propolis was also investigated on the existence of alkaloids, flavonoids, saphonins,tannins, steroids, and terpenoids. Ethanol extract of Trigona spp. propolis showed antibacterial activity onSalmonella sp. with minimum inhibitory concentration of 0,87% (w/w). The compound groups detected inethanol extract Trigona spp. propolis were flavonoids and tannins, which suggests that the antibacterial activityof Trigona spp. propolis may be due to these compounds.Â Keywords: propolis, Trigona spp., Salmonella sp., antibacterial